Modern labor Economics : Theory and Public Policy - EHRENBERG, Ronald G (Addison-Wesly Pub, 2003)
The best-selling Modern Labor Economics provides a clear, comprehensive introduction to labor-market behavior. In addition to presenting core theory, Ehrenberg and Smith provide empirical evidence for or against each hypothesis, explore the usefulness of various theories for public policy analysis, and include detailed policy examples in each chapter.